Metasynthesis of Research on the Role of Psychiatric Inpatient Nurses: What Is Important to Staff?. (March 2014) - Delaney, Kathleen R.; Johnson, Mary E.
BACKGROUND: Inpatient psychiatric nurses are a large workforce, but their work is poorly articulated and thus poorly understood outside of the professional inpatient community.OBJECTIVE: To learn how inpatient psychiatric nurses depict their work, define important aspects of their role, and view the impact of the unit environment on their clinical practice.DESIGN: Metasynthesis of research that has focused on the ideas and perceptions of inpatient psychiatric nurses around their role and practice on inpatient psychiatric units.RESULTS: Three themes emerged from the analysis; the first was an umbrella for three important aspects of nursing work: the nurses' efforts to forge engagement with patients; their activities which maintained the safety of the unit and interventions nurses viewed as educating/empowering patients. The second theme captures the conditions that enabled nurses to do this work such as a cohesive nursing team and their sense of self-direction in their role. The final theme centers on difficulties nurses encountered in enacting their role which included multiple responsibilities for patient care and management of the milieu; intense work often with low visibility and scant support within the organization.CONCLUSIONS: Nurses need to articulate their practice so they can assert for the staffing and resources needed to keep units safe and promote patients' well-being, strive toward quality, and promote the development of the specialty.